PENELITIAN DAN SUMBANGANNYA TERHADAP ILMU PENGETAHUAN (SAINS) - Mo’tasim (Sekolah Tinggi Agama Islam Hasan Jufri Bawean, 2017)
Now a day there is a tendency someone see science as a product, less attention to the process. They have no attempt to find formulas, propositions, or new theories and try to control and forecast, just simply accept. In the context of seeking the truth, the true truth is done through the Apocalypse Approach. The truth based on revelation is absolute truth, because it is based on belief and belief. Then Discovery of the Truth Through a Non-Scientific Approach. Knowledge-carrying knowledge does not always go through scientific procedures and processes, this tends to be intuitive. Discovery of truth through a common sense approach This approach is usually less acceptable as a scientific truth. Then Discovery of truth through accidental approach The discovery of truth through accidental approach is not a scientifically-acquired truth, Discovery of truth through trial and error approach. The discovery of truth through an intuitive approach, The discovery of truth through an intuitive approach is obtained through an unconscious process without the use of reasoning and the process of scientific thinking. And the discovery of truth through the approach of authority. The discovery of truth through the Scientific Approach. That is the method of seeking the truth done by the philosophers. Research is very important in order to find the truth about science and science, History proves the excitement of research practice so that the impact on the fertile of science discoveries. Just how these sari lessons become our best teachers to get the spirit to do research, researching to find the truth, and increase the piety to Allah SWT.